The Impact of Online Gaming on Students’ Emotional Well-Being and Academic Achievement at MA Nurul Iman Montong Baik - Zaini, Muh. Ihwan; Hariadi; Hary Septianwari; Didik Daniyantara (The Future of Education Journal, 2025)
The rapid development of information technology, particularly the internet, has influenced various aspects of human life, including education and entertainment. One of the most popular forms of entertainment today is online gaming, which has gained significant interest among students. This study aims to analyze the impact of online gaming on the emotional mental condition and academic achievement of students at MA Nurul Iman Montong Baik. This research employed a descriptive quantitative method with a cross-sectional design. The study population consisted of 69 students, with a sample of 30 respondents selected using purposive sampling. Data were collected through a questionnaire that had been tested for validity and reliability, and then analyzed using descriptive statistics with SPSS software. The results indicate that online games have a negative effect on students’ emotional mental conditions, where excessive playing intensity causes anxiety, irritability, and decreased learning concentration. However, the correlation test showed no significant relationship between the intensity of online gaming and students’ academic achievement (r = 0.099; p = 0.603). Thus, it can be concluded that online gaming affects psychological aspects more strongly than academic aspects. Therefore, the role of teachers and parents is crucial in supervising and guiding students to use online games wisely and in moderation.